The turn-taking mechanism in classroom interactions of public high school 2 Ambon - Carolina Sasabone (Journal of Education and Learning (EduLearn), 2019)
A special feature of class interaction discourse relates to typical elements of context. The elements of the context include the participants, the background, the topic, the nature of the message, and the message tone. Teachers are more dominant to organize the course of teaching and learning activities, such as topic selection, topic development, and control of conversation topics or learning topics. Teachers determine the direction of a conversation or turn-taking, ie when an opportunity is given to students to speak and when to take the rotation-said. The characteristics of learning conversations are (1) the participants are teachers and students, (2) the conversation is done during the teaching and learning activities, (3) the conversation has a purpose, and the topic is related to the learning objectives. . In addition teachers also have certain rights that usually appear in the teacher-centered classroom. These rights include (a) participating in all interactions, (b) initiating interactions, (c) determining the time to participate, (d) determining who is given the opportunity to interact, (e) determining who gets a turn more than once, and (f) closing the interaction. The mechanism of teacher-student turn-taking in classroom learning activities can be done by (1) getting opportunities (2) stealing opportunities, (3) seizing opportunities, (4) replacing, and (5) continuing.